Step 1 :
Equation at the end of step 1 :
4x
—————————————— ÷ 5 ÷ (x + 6)
((x2) + 32x18)
Step 2 :
4x
Simplify —————————
9x18 + x2
Step 3 :
Pulling out like terms :
3.1 Pull out like factors :
9x18 + x2 = x2 • (9x16 + 1)
Dividing exponential expressions :
3.2 x1 divided by x2 = x(1 - 2) = x(-1) = 1/x1 = 1/x
Equation at the end of step 3 :
4
—————————————— ÷ 5 ÷ (x + 6)
x • (9x16 + 1)
Step 4 :
4
Divide —————————— by 5
x•(9x16+1)
Equation at the end of step 4 :
4
——————————————— ÷ (x + 6)
5x • (9x16 + 1)
Step 5 :
4
Divide ——————————— by x+6
5x•(9x16+1)
Final result :
4
—————————————————————————
5x • (9x16 + 1) • (x + 6)